Profile of Patients with Viral Infection at the Dermatology and Venereology Outpatient Unit of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, in 2016-2018 - Putri, Melati Adinda; Astari, Linda; Bramantono, Bramantono; Anggraeni, Sylvia (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2025)
Highlights: The most common viral skin infections at the Dermatology and Venerology Outpatient Unit of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, in 2016-2018 were shingles, verruca vulgaris, varicella, molluscum contagiosum, and measles. Viral skin infections predominantly affected late teens (17-25 years old), females, and each disease presented different clinical manifestations and treatments.   Abstract Introduction: The high incidence of viral skin infections in Indonesia, combined with a lack of understanding of risk factors and prevention measures, poses a significant problem. Few studies have examined the epidemiological profile of viral skin infections in Indonesia. This study aimed to evaluate the profile of patients with viral infections at the Dermatology and Venereology Outpatient Unit of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, from 2016 to 2018. Methods: This was a descriptive, retrospective study based on the medical records of 560 patients collected between January 2016 and December 2018 (n=560). All data calculations were performed using the International Business Machines Corporation (IBM) Statistical Package for Social Sciences (SPSS) version 26. Results: The prevalence of the five viral infections was 71.8% among all patients with viral infections. The most common diagnosis was shingles (47.5%), the most affected age group was late teens (17-25 years old) (21.3%), the most common gender was female (52,9%), the most frequent clinical manifestation was vesicles (52.1%), and the most commonly used therapy type was topical (73.4%). Conclusion: The number of patients with viral infections at the Dermatology and Venereology Outpatient Unit of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, has increased annually, requiring more comprehensive management to reduce morbidity and mortality.